2002
DOI: 10.1109/jstqe.2002.801689
|View full text |Cite
|
Sign up to set email alerts
|

Er-doped AlGaAs native oxides: photoluminescence characterization and process optimization

Abstract: We present 300 K photoluminescence (PL) characterization data for wet thermal native oxides of Al 0 58 Ga 0 42 As films grown by metal organic chemical vapor deposition and doped with Er via multiple high-energy ion implants (for 0.0675, 0.135, and 0.27 atomic percent (at.%) peak Er concentrations), and Al 0 5 Ga 0 5 As and Al 0 8 In 0 2 As films doped with Er (0.03-0.26 at.%) during molecular beam epitaxy crystal growth. Broad spectra with a 50-nm full-width at half-maximum and a PL peak at 1.534 m are observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…We have shown in studies reported elsewhere that AlGaAs native oxides are a viable host for optically active Er 3+ , supporting strong room temperature photoluminescence. [9][10][11] In our first demonstration of fully oxidized single-heterostructure ͑1.4 m Al 0.4 Ga 0.6 As/ 1.0 m Al 0.8 Ga 0.2 As͒ planar waveguides, an optical loss of ␣ = 2.5 cm −1 ͑10.9 dB/cm͒ was obtained at 0 = 1.55 m, while absorption of the external field by the substrate prevented characterization above the GaAs bandgap energy. 6 Conversion of a semiconductor heterostructure to an oxide heterostructure may also provide a means for realizing a mode expander.…”
mentioning
confidence: 96%
“…We have shown in studies reported elsewhere that AlGaAs native oxides are a viable host for optically active Er 3+ , supporting strong room temperature photoluminescence. [9][10][11] In our first demonstration of fully oxidized single-heterostructure ͑1.4 m Al 0.4 Ga 0.6 As/ 1.0 m Al 0.8 Ga 0.2 As͒ planar waveguides, an optical loss of ␣ = 2.5 cm −1 ͑10.9 dB/cm͒ was obtained at 0 = 1.55 m, while absorption of the external field by the substrate prevented characterization above the GaAs bandgap energy. 6 Conversion of a semiconductor heterostructure to an oxide heterostructure may also provide a means for realizing a mode expander.…”
mentioning
confidence: 96%